2004
DOI: 10.1023/b:pham.0000033014.04820.a7
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of the Carborane Derivative of Cholesteryl Ester by Glioma Cancer Cells Is Mediated Through LDL Receptors

Abstract: These results strongly suggested that the cellular uptake of BCH (in liposomal formulation) by SF-763 and SF-767 glioma cell lines is mediated through LDL receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…MA), is being used clinically in photodynamic therapy for age-related macular degeneration (Ichikawa 2004). Verteporfin is transported in the plasma primarily by lipoproteins (especially low-density lipoproteins), are known to deliver hydrophobic materials to tumor cells (de Smidt et al 1993;Koller-Lucae et al 1999;Pan et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…MA), is being used clinically in photodynamic therapy for age-related macular degeneration (Ichikawa 2004). Verteporfin is transported in the plasma primarily by lipoproteins (especially low-density lipoproteins), are known to deliver hydrophobic materials to tumor cells (de Smidt et al 1993;Koller-Lucae et al 1999;Pan et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous observations demonstrated that the carborane derivatives had a potent selective inhibition effect on the proliferation of the cancer cell lines and no effect on normal cell lines [37]. It was also observed that carborane derivatives can lead to specific binding modalities with macromolecules, such as myoglobin [38], hemoglobin [39], nicotinamide phosphoribosyltranferase [40], low-density lipoprotein [41], relevant carborane ligands had been considered as effective pharmacophores as non-BNCT anticancer agents [42][43][44]. Based on these considerations, it is possible to readily utilize the novel carborane derivatives to target and distinguish different kinds of cells for the specific cancer diagnostics and treatment.…”
Section: Specific Recognition Of Cancer Cellsmentioning
confidence: 99%
“…31,32) However, the purpose of liposomal formulation in this study was not for reducing side effects, but for making injectable form of hydrophobic drugs. 33) Furthermore, it is possible that rhinacanthins transferred to serum lipoprotein effectively accumulated in tumor tissues, since lipoproteins, especially low density lipoproteins, are known to deliver hydrophobic materials to tumor cells. [33][34][35][36] In the present study, the results demonstrated for the first time that rhinacanthins-N, -Q and -C entrapped in liposomes showed antiproliferative activities against HeLaS3 cells: The activities were slightly higher than that of free drugs after 24-and 48-exposure.…”
Section: Fig 3 Antiproliferative Activities Of Liposomal Rhinacanthmentioning
confidence: 99%